IT'S TIME TO LOOK TO THE WEST: A NEW INTERPRETATION ON HOMO ERECTUS FINDINGS DISTRIBUTION OF JAVA: SAATNYA MENENGOK KE BARAT: SEBUAH INTERPRETASI BARU TENTANG DISTRIBUSI TEMUAN HOMO ERECTUS DI JAWA - Widianto, Harry; Noerwidi, Sofwan (BRIN, 2020)
Abstract Paleontological data indicate that the beginning of Java Islandia occupation occurred at the Plio-Pleistocene boundary, around 2.4 Mya. However, the oldest Homo erectus fossil was found in Sangiran, around 1.5 Mya. Recently, Pleistocene sites were discovered from the western part of Java, e.g. Rancah, Semedo, and Bumiayu. This paper describes the significance of archeological, paleontological, and especially paleoanthropological data from the new sites, and their implications to the future Quaternary prehistory research strategies determination. Data collection methods include literature study and surveys, while analysis is carried out on the geological, archeological, paleontological, and paleoanthropological data. The result shows the dispersal of Homo erectus is extended to the western part of Java, between 1.8-1.7 Mya, older than the oldest Homo erectus of Sangiran. A new window of the human arrival on this island is identified. So, it is time to look to the west, and intensive research should be carried out to those areas. Abstrak Data paleontologis menunjukkan bahwa awal penghunian Jawa terjadi pada batas Plio-Plestosen sekitar 2.4 juta tahun lalu, namun fosil Homo erectus tertua yang ditemukan di Sangiran, berasal dari lapisan 1.5 juta tahun lalu. Belakangan ini, ditemukan situs-situs Plestosen, dari bagian barat Pulau Jawa, yaitu Rancah, Semedo, dan Bumiayu. Tulisan ini bertujuan untuk menampilkan signifikansi data arkeologi, paleontologi dan terutama paleoanthropologi dari situs-situs tersebut, serta implikasinya bagi penentuan strategi penelitian prasejarah kuarter di masa depan. Metode pengumpulan data meliputi studi pustaka, dan survei pada ketiga situs tersebut. Analisis data dilakukan pada data geologis, arkeologis, paleontologis dan paleoantropologis. Hasilnya, distribusi lateral Homo erectus semakin luas di bagian barat Jawa, dengan kronologi 1.8-1.7 juta tahun, lebih tua dibanding Homo erectus tertua dari Sangiran. Sebuah jendela baru tentang kedatangan Homo erectus di Pulau Jawa telah teridentifikasi. Implikasinya, sudah saatnya penelitian prasejarah kuarter intensif dilakukan di bagian barat pulau ini.